Automated structure elucidation of two unexpected products in a reaction of an alpha,beta-unsaturated pyruvate. - Sharman, G; Jones, I; Parnell, M; Willis, M; Mahon, M; Carlson, D; Williams, A; Elyashberg, M; Blinov, K; Molodtsov, S (2004)
The reaction between an alpha,beta-unsaturated pyruvate and ethyl diazoacetate (EDA) yielded two unexpected products. The structures of these products were determined by automated elucidation of the chemical structures using spectroscopic inputs of a series of 1D and 2D NMR data using the computer program ACD/Structure Elucidator, StrucEluc. The formation of these products is rationalised. Their structures were also confirmed by x-ray crystallography.